Utility of Shear Wave Elastography for Diagnosing Chronic Autoimmune Thyroiditis. (16th July 2015) - Fukuhara, Takahiro; Matsuda, Eriko; Izawa, Shoichiro; Fujiwara, Kazunori; Kitano, Hiroya
Abstract : The aims of this study were to evaluate the utility of shear wave elastography (SWE) using acoustic radiation force impulse (ARFI) for diagnosing chronic autoimmune thyroiditis (CAT) and to verify the effect of fibrotic thyroid tissue on shear wave velocity (SWV). The subjects were 229 patients with 253 normal thyroid lobes (controls) and 150 CAT lobes. The SWV for CAT (2.47 ± 0.57 m/s) was significantly higher than that for controls (1.59 ± 0.41 m/s) (P < 0.001 ). The area under the receiver operating characteristics (ROC) curve for CAT was 0.899, and the SWV cut-off value was 1.96 m/s. The sensitivity, specificity, and diagnostic accuracy were 87.4%, 78.7%, and 85.1%, respectively. Levels of anti-thyroperoxidase antibodies and thyroid isthmus thickness were correlated with tissue stiffness in CAT. However, there was no correlation between levels of anti-thyroglobulin antibodies and tissue stiffness. Quantitative SWE is useful for diagnosing CAT, and it is possible that SWE can be used to evaluate the degree of fibrosis in patients with CAT.